Hubungan Antara Motivasi Belajar Dengan Prestasi Belajar Siswa Di SMP Negeri 1 Tiganderket, Karo Sumatera Utara - Pancar Surya Purba (LPPM Politeknik Pratama, 2024)
The problem in this research is the low motivation and learning achievement of students at SMP Negeri 1 Tiganderket. The aim of this research is to determine the relationship between learning motivation and student learning achievement. This research is quantitative correlational research which aims to examine the correlation of two variables. Determining the sample in this study used a total sampling technique, so that the number of samples was the same as the population, namely 87 students. The data collection techniques used are learning motivation questionnaires and learning achievement documents, while the analysis techniques used are linearity tests and product moment correlation tests. Determining the research sample used the Total Sampling technique so that the population and sample had the same number, namely 69 class II students at SD Negeri 101777 Saentis for the 2013/2014 academic year. The research results showed that: (1) students' learning motivation had an average score of 76.76 in the medium category, the highest motivation was 95.45 in class IX and the lowest motivation was 49.43 in class VII; (2) student learning achievement has an average score of 82.18 in the medium category, the highest achievement of 95.17 is in class IX and the lowest achievement of 70 is in class VII and IX; and (3) the results of the correlation test show that there is a significant relationship between learning motivation and student learning achievement at SMP Negeri 1 Tiganderket. This is based on data that the rcount value, namely 0.862, is greater than the rtable value, namely 0.2115, and the sig value. (2-tailed), which is 0.000, is smaller than the α value, which is 0.05, so Ha is accepted and H0 is rejected. Thus, it can be proven that learning achievement will be in the high category if learning motivation is in the high category.